Implementasi Teknologi Smart Hybrid Dryer pada Kelompok Petani Kopi Kelurahan Gombengsari - Ikhwanul Qiram; Sutami Dwi Lestari; Adi Mulyadi (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The coffee industry in Banyuwangi has a rich history, dating back to Dutch colonial rule. Despite its prominence, coffee farmers, especially the Tunas Harapan farmer group in Gombengsari, face significant challenges in post-harvest coffee handling, particularly in drying methods. Traditional sun-drying methods employed by the farmers are inefficient and fail to meet market standards, leading to reduced product quality. To address this issue, this community engagement project introduced the Solar Hybrid Dryer (SHD) technology, a sustainable drying method combining solar and electric heating. The project involved designing and constructing SHD units integrated with IoT systems for real-time monitoring and control. Additionally, solar panels were installed to provide renewable energy for the system, minimizing operational costs. Training sessions were conducted for 15 members of the Tunas Harapan group, focusing on post-harvest coffee handling and the use of SHD technology. The training aimed to improve farmers' knowledge and skills, enhancing the quality of their coffee products. The SHD technology proved effective, reducing drying time from 15 days to 5 days while maintaining the optimal moisture content of 12%. Post-training surveys indicated high levels of satisfaction among participants, with improvements in product quality and increased potential for collaboration. Overall, the implementation of SHD technology and capacity building has provided sustainable solutions for improving the livelihoods of coffee farmers in Gombengsari